Labor Reallocation over the Business Cycle: New Evidence from Internal Migration - Saks, Raven E.; Wozniak, Abigail (Journal of Labor Economics, 2011)
This article establishes the cyclical properties of a novel measure of worker reallocation: long-distance migration rates within the United States. Combining evidence from a number of data sets spanning the entire postwar era, we find that internal migration within the United States is procyclical. This result cannot be explained by cyclical variation in relative local economic conditions, suggesting that the net benefit of moving rises during booms. Migration is most procyclical for younger labor-force participants. Therefore, cyclical fluctuations in the net benefit of moving appear to be related to conditions in the labor market and the spatial reallocation of labor.